Determination of Triterpenoid Saponins (Quillaja saponaria Molina) from Roots of Withania somnifera (L.) Dunal by High Performance Liquid Chromatography - Wankhede, Sonal; Saxena, Mohini; Yadav, Bhisham (Asian Journal of Chemistry, 2010)
Saponins are a class of chemicals found in natural sources with soapy character due to their surfactant properties. Saponins are often referred to as a "natural detergents" because of their foamy texture. On hydrolysis they yield a variety of sugar detergents. In Withania somnifera saponins contain an additional acyl group (sitoindosides VII and VIII) and exhibit characteristics such as strong foaming power in aqueous solutions from which the name 'saponins' has been derived. Saponin rich extracts of the Chilean indigenous tree Quillaja saponaria Molina are widely used as natural foaming agents in foods and beverage, food emulsifiers, photographic emulsions, vaccine adjuvants, etc. This work describes the determination of the Chilean quillaja tree (Quillaja saponaria Molina) as alternative low cost surfactant. This present study was carried out to evaluate determination of Quillaja saponaria Molina triterpenoid saponins from the roots of Withania somnifera. The reverse phase-high performance liquid chromatography (RP-HPLC) method was successfully applied to determine triterpenoid saponins content in the two samples of roots of Withania somnifera from two different places, namely Ujjain, Madhya Pradesh, India and Bhopal, Madhya Pradesh, India which provide a new basis of overall assessment on quality of Withania somnifera.